IMPLEMENTASI KEBIJAKAN JAMINAN SOSIAL KETENAGAKERJAAN DI KOTA PEKANBARU - Novriana Hafizhah; Hasim As’ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Implementation of the policy is a tool of administration of law where various factors, organization, procedures and techniques that work together to carry out the policy in order to achieve the target or goal that is desired. Law no.24 of 2011 concerning the social security agency is the regulation for protect the workforce. Which becomes the attention of major in the study of this is the policy of employment social security by law no.24 of 2011, which become the problem is there are companies that have not registered their workers as participants BPJS Employment. The purpose of this study is to determine the implementation and inhibiting factors of employment social security policy in Pekanbaru. The concept of the theory which is used the theory of the implementation of the policy by Charles O’ Jones (Agustino, 2017) is an organization, interpretation and application. Research is using the methods of descriptive qualitative by using technique purposive sampling with the technique of collecting data on observation, interviews and documentation. The result of this study indicate that the implementation of the employment social security policy in Pekanbaru still not optimal, especially in the criteria of interpretation and application. The factors inhibiting is lack of education and socialization that is done by BPJS Employment and communicating against the company which led to a lack of knowledge and information that received by the workers.Keywords: Implementation, Policy, Employment Social Security Agency